Manutenção da coloração da lichia frigorificada com a utilização de ácidos orgânicos - Souza, Angela Vacaro de [UNESP]; Vieites, Rogério Lopes [UNESP]; Kohatsu, Douglas Seijum [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (My University, 2009)
The objective of this research was to evaluate the influence of organic acids in different concentrations in the coloration of lychee fruits. The fruits were treated by: immersion of the fruits for 15 minutes in ascorbic acid 1% (T2); ascorbic acid 2% (T3); ascorbic acid 3% (T4); citric acid 1% (T5); citric acid 2% (T6); citric acid 3% (T7) and the control (T1), packaged in polystyrene trays and polyvinyl chloride film with 0.020 mm and stored in BOD at 5°C and 90 ± 5% of RH. The experimental delineation was in scheme completely randomized, with 6 times of storage for the analysis of coloration and enzymatic and until reach the limit of marketing for the analysis of shelf-life, being the fruits analyzed from each 3 days with 3 replicates of 10 fruits by experimental unit. The parameters evaluated were: visual analysis of the browning, coloration and specific activity of the polyphenol oxidase and the peroxidase. The use of the ascorbic acid to 3% was more effective in maintaining the coloration of the fruits and in decrease of the enzymatic activity.

O objetivo do trabalho foi avaliar a influência dos ácidos orgânicos em diferentes concentrações na coloração de frutos de lichia. Os frutos foram tratados por: imersão dos frutos por 15 minutos em ácido ascórbico a 1% (T2); ácido ascórbico a 2% (T3); ácido ascórbico a 3% (T4); ácido cítrico a 1% (T5); ácido cítrico a 2% (T6) ácido cítrico a 3% (T7) e o controle (T1), embalados em bandejas de poliestireno expandido e filme de policloreto de vinila 0,020mm e armazenados em B.O.D. a 5ºC e 90±5 % de UR. O delineamento experimental foi em esquema inteiramente casualizado, com 6 tempos de armazenamento para as análises de coloração e enzimática e até atingirem o limite de comercialização para a análise da vida útil, sendo os frutos analisados a cada 3 dias com 3 repetições e 10 frutos por unidade experimental. Os parâmetros avaliados foram: análise visual do escurecimento, coloração e atividade específica da polifenol oxidase e da peroxidase. A utilização de ácido ascórbico a 3% mostrou-se ser o mais eficaz na manutenção da coloração dos frutos e na diminuição da atividade enzimática.
Maintenance of lychee's cold storaged coloration using organic acids
Keywords: Litchi chinensis; Enzymatic browning; Color; Litchi chinensis; Escurecimento enzimático; Cor